Behavioral Determinants of Independent Umrah Preference Among Indonesian Generation Z: Evidence From PLS-SEM - Armanditto, Muhammad Ashshiddiq; Zaim, Ilma Aulia (Dinasti Publisher, 2026)
Indonesia’s Umrah sector underwent a major regulatory transformation with the enactment of UU No. 14/2025, which formally permits independent Umrah (Umrah Mandiri) as an alternative to travel through registered operators (PPIU). This study investigates the determinants of Indonesian Generation Z Muslims’ preference for independent Umrah using an extended Theory of Planned Behavior (TPB) integrated with the Technology Acceptance Model (TAM) and Value Perception Theory. Seven constructs were examined: Digital Readiness, Perceived Cost Advantage, Attitude, Subjective Norm, Perceived Behavioral Control, Behavioral Intention, and Choice Preference. Data were collected from 245 Generation Z Muslim respondents through an online survey and analyzed using PLS-SEM in SmartPLS 4. The results supported five of seven hypotheses. Digital Readiness significantly influenced both Attitude and Perceived Behavioral Control, while Perceived Behavioral Control was the strongest predictor of Behavioral Intention, followed by Subjective Norm. Behavioral Intention emerged as the strongest determinant of Choice Preference for independent Umrah. In contrast, Perceived Cost Advantage did not significantly affect Attitude, and Attitude did not significantly influence Behavioral Intention. These findings indicate that Generation Z’s preference for Umrah Mandiri is driven primarily by digital capability and self-efficacy rather than cost considerations, offering practical implications for PPIU operators, digital service providers, and policymakers.